Redes Metal Orgánicas de Plata como Inhibidores Bacterianos - Loera-Serna, Sandra (2022)
Currently the development of new materials with potentialized properties is a challenge for the scientific community, particularly those that function as bactericides. The study of structures containing silver has increased in recent decades thanks to the synthesis of nanoparticles, which have various properties of interest, including bactericidal effects. We have sought to have materials that can contain silver in metallic or ionic form and with properties that allow them to act against various disease-causing organisms, such as bacteria. This work addresses the main results of a new type of hybrid materials called metal organic frameworks, or MOFs, that are formed by metal centers and organic ligands joined by coordination bonds. Additionally, the most important details of the use of silver in the construction of MOFs and its bactericidal effect will be explored, opening to the reader a panorama about the synthesis and characteristics of this new nanostructured materials.